Industrial power engineering handbook - Agrawal, K. C. (Butterworth-Heinemann, 2001)
Never before has so much ground been covered in a single volume reference source. This five-part work is sure to be of great value to students, technicians and practicing engineers as well as equipment designers and manufacturers, and should become their one-stop shop for all information needs in this subject area. This book will be of interest to those working with: Static Drives, Static Controls of Electric Motors, Speed Control of Electric Motors, Soft Starting, Fluid Coupling, Wind Mills, Generators, Painting procedures, Effluent treatment, Electrostatic Painting, Liquid Painting, Instrume.
Keywords: Factories -- Power supply -- Handbooks, manuals, etc.; elektronické knihy; electronic books